(untitled) - Ye, Nong (Hoboken, NJ, 2008)
Secure Computer and Network Systems: Modeling, Analysis and Design is an up-to-date resource for practising engineers and researchers involved in security, reliability and quality management of computer and network systems. It is also a must-read for postgraduate students developing advanced technologies for improving computer network dependability.
Keywords: Computer networks,Computer networks,Computer security,Mạng lưới máy tính,Mạng lưới máy tính,Bảo mật máy tính; Security measures,Design and construction,Thiết kế và xây dựng,Tiêu chuẩn bảo mật